A case report of molar pregnancy in a 52 year old woman - M Javadian (Babol University of Medical Sciences, 2001)
Objective: Although molar pregnancy is rare among women over 50 years old, but due to the risk of persistent and malignant trophoblastic disease in women over 40 years old it is very important. Case: The case was a 52-year-old woman with complaint of vaginal bleeding started from 4 months prior to admission. According to the result of abdominal sonography, a 91×112 mm mass with mixed echogenicity in fundus of uterus with myoma diagnosis was reported. Clustered vesicles (Molar pregnancy) were observed after abdominal hysterectomy and incision of uterus. Diagnosis was confirmed by pathology. Conclusion: Sonography is very helpful in diagnosis of molar pregnancy but is not necessarily enough. Urinary pregnancy test is not accurate enough for diagnosis of molar pregnancy. In premenopausal age group, pregnancy complications such as molar pregnancy must be considered as an important differential diagnosis of abnormal uterine bleeding. Regarding the age of the patient and the fact that she didn’t want to have any more children, abdominal hysterectomy was performed and as a prophylactic measure, we measured βHCG. And the results showed no malignancy.